3y=-2x+2

Simple and best practice solution for 3y=-2x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y=-2x+2 equation:


Simplifying
3y = -2x + 2

Reorder the terms:
3y = 2 + -2x

Solving
3y = 2 + -2x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '3'.
y = 0.6666666667 + -0.6666666667x

Simplifying
y = 0.6666666667 + -0.6666666667x

See similar equations:

| .50x=1500 | | 8x-3=4x+39 | | -70+2x+8x=70 | | (2y+20)= | | f(x)=x^2+11x+0 | | 63x-35= | | 3x^2-2x-100=0 | | r^16+5=11 | | 45x=25-5y | | 4x+3y=y+8 | | -4n+16=116 | | 2100=x*60 | | 5y=25-45x | | 2h(4h+3)= | | 18y-18=18 | | -w^7-2=19 | | log(x+6)=log(8x)-log(3x+2) | | 6x+10+4x+40=180 | | 4n+16=116 | | 2y+10-y=-7 | | -(2-3b)=2(3b-4) | | 4n+16=16 | | 4(2x-y)+11=8x-13 | | 3a+5=2a+17 | | 6x+19=-30 | | 3x-9=5x+15 | | 14x-9=21+4x | | 3t+4t=51-8 | | (-5)+4=x-3 | | 3(u+3)=-6(4u-1)+9u | | (6x+40)-2x=(2x+116)-2x | | y-11=-17 |

Equations solver categories